Evaluation of Bacillus coagulans LMG S-31876 for immunomodulation and stress: a double-blind, placebo-controlled clinical trial - Kallur, Ranjith Kumar; Madapati, Sreenadh; Banerjee, Mayuri; Mathur, Ankita; Bhattacharya, Sourish (Frontiers in Nutrition, 2025)
ObjectiveThe study aimed to analyze the safety and effectiveness of the ProBC Plus (Bacillus coagulans LMG S-31876) supplement across various health parameters, including stress levels, immunoglobulin levels, biochemical parameters, and vital signs.MethodsA randomized, double-blind, placebo-controlled clinical trial study was conducted involving 50 subjects diagnosed with ailments related to immune system dysfunction and stress related disorders. Patients were treated with ProBC Plus (2 billion colony-forming units [CFU]) along with a placebo capsule administered once daily for a period of 8 weeks.ResultsThe effects of ProBC Plus exhibited a positive response on stress relief, lipid parameters, immune status, and vital signs, which is further statistically significant (p value <0.05, 5% marginal error at 95% CI).ConclusionThe study on ProBC Plus showed positive results. Over the course of 8 weeks, an improvement in the immune status was observed, as indicated by the immune status questionnaire. Enzymatic markers exhibited a significant decline in predicting a positive response toward treatment. In terms of lipid profile, ProBC Plus helps to maintain the value within the normal range, thereby predicting its potential as cardiovascular support. The vital signs remained within the normal range throughout the study. Therefore, ProBC Plus is considered safe for consumption and contributes to the overall well-being of individuals.Clinical trial registrationhttps://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=77914&EncHid=24313.96864&userName=CTRI/2023/01/048720, CTRI/2023/01/048720.